Discovery of selective cystathionine β-synthase inhibitors by high-throughput screening with a fluorescent thiol probe12. Issue 1 (23rd November 2016) - Niu, Weining; Wu, Ping; Chen, Fei; Wang, Jun; Shang, Xiaoya; Xu, Chunlan
Abstract : Screening of a natural product library identified several selective cystathionine β-synthase inhibitors, which suppressed the proliferation of HT29 cancer cells. Abstract : A high-throughput assay was developed to identify inhibitors of cystathionine β-synthase (CBS), which is one of three key enzymes involved in H2 S biosynthesis. Screening of 6491 natural compounds identified several selective CBS inhibitors, which suppressed the proliferation of HT29 cancer cells, with IC50 values of less than 10 μM.